Layer Controllable Graphene Using Graphite Intercalation Compounds with Different Stage Numbers through Li Conversion Reaction. Issue 3 (11th December 2015) - Wang, Fei; Chen, Guorui; Li, Wei; Wang, Yonggang; Wang, Congxiao; Zhang, Yuanbo; Xia, Yongyao
Abstract : Graphene with controlled stacking numbers and fewer defects is synthesized through an electrochemical approach using metal chloride graphite intercalation compounds (GICs) via a lithium conversion reaction. Using GICs with different stage numbers as precursors, graphene with different layers is successfully obtained. The mobility estimated from the transport measurement is around 4000 cm 2 V −1 s −1, which is comparable to the micromechanically cleaved bilayer graphene.